Smart Grid Energy Reduction and QoS Maximization through Renewable Energy and Data Buffering - Patchamuthu, Karunakaran (Journal of Electrical Engineering and Automation, 2024)
The integration of renewable energy sources and advanced data management strategies is pivotal for the evolution of smart grids. This research focuses on optimizing energy consumption and enhancing Quality of Service (QoS) in smart grids by leveraging renewable energy and implementing data buffering techniques. The proposed data buffering integrated renewable smart grid framework reduces the dependance on conventional energy sources, minimizes energy costs, and improves service consistency. Through a detailed analysis and experimental validation, the proposed study demonstrates significant improvements in energy efficiency and QoS metrics, showcasing the potential of the proposed approach in modern smart grid environments.